2019
DOI: 10.1097/pai.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of p16 Expression on Cancer and Stromal Cells With Clinicopathologic and Immunohistochemical Features of Lobular Breast Carcinoma

Abstract: Background: Cancer-associated fibroblasts, play a central role in the tumor-stroma interaction and promote tumorigenesis. However, it is still unclear how these processes are regulated. The aim of this study is to investigate p16 expression in cancer and stromal cells of invasive lobular carcinoma (ILC). Design: Clinicopathologic parameters and immunohistochemical stains for estrogen receptor (ER), progesterone receptor, E-cadherin, and human epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Additionally, restoration of p16 expression in stromal fibroblasts suppressed cancer cell migration and invasion. Thus, these findings proposed positive stromal p16 expression as a treatment strategy to prevent nodal or distant metastasis [98].…”
Section: Tumor Suppressive Components Of Cell Cyclementioning
confidence: 92%
“…Additionally, restoration of p16 expression in stromal fibroblasts suppressed cancer cell migration and invasion. Thus, these findings proposed positive stromal p16 expression as a treatment strategy to prevent nodal or distant metastasis [98].…”
Section: Tumor Suppressive Components Of Cell Cyclementioning
confidence: 92%
“…On the contrary, p16 was not or was weakly expressed in cancer cells [ 46 ]. Furthermore, stromal p16 overexpression was observed in atypical polypoid adenomyoma [ 47 ], breast carcinoma [ 48 , 49 ], and adult granulosa cell tumors of the ovary [ 50 ], suggesting the occurrence of stromal cell senescence. In one other study, senescent T-cell infiltration was identified in the stromal compartment of colorectal cancer tissues [ 51 ].…”
Section: The Discovery Of Senescent Stromamentioning
confidence: 99%
“…IHC was performed on the collected samples as previously described. 15 Briefly, the slides of LUAD tissues were dewaxed with xylene and rehydrated with graded ethanol. Then, heat mediated antigen retrieval was conducted with citrate buffer for UVE2V2 detection and with ethylene diamine tetraacetic acid buffer for PD-L1 detection.…”
Section: Immunohistochemistry (Ihc) and Ihc Scoringmentioning
confidence: 99%